Hindavī bhāshā aura usakā sāhitya : viśesha sandarbha Śekha Aśarapha kā Nausarahāra - Gauṛa, Chaganalāla Bholārāmajī (Sāhitya Ratnālaya, 1979)
Study of Dakhini Hindi and its literature; includes an edited text of the elegy Nausarahāra by Śekha Aśarapha, 16th century.